Penegakan Hukum Pidana Lingkungan Dalam Mewujudkan Tata Nilai Keadilan Lingkungan Hidup - Budi Handoyo (TAQNIN: Jurnal Syariah dan Hukum, 2020)
Environmental damage in Indonesia is getting more and more concerning. In fact, it has endangered every creature, including the life of future generations. Through legal means it can be seen how the law should be implemented. Therefore, environmental law enforcement can be interpreted as the use or application of instruments and sanctions in the legal field. Law Number 32 of 2009 concerning Environmental Protection and Management regulates environmental problems as a basic guideline for law enforcement officials to prosecute perpetrators of environmental crimes subject to criminal penalties according to applicable regulations. Criminal law enforcement in this law introduces the threat of minimum and maximum penalties, expansion of evidence, punishment for violations of quality standards, integrated criminal law enforcement, and regulation of corporate crime